Pemanfaatan Program Makan Bergizi Gratis Berdasarkan Teori ABC : Studi Kasus Siswa yang Tidak Memanfaatkan MBG di SD Negeri 100 Kendari - Dhea Sakila; Hartati Bahar; Putu Eka Meiyana Erawan (Lembaga Pengembangan Kinerja Dosen, 2026)
The issue of nutrition among school children remains a public health challenge in Indonesia. As an effort to improve the nutritional status of students, the government launched the Free Nutritious Meal program (MBG) in educational units. However, in its implementation, there are still students who do not take advantage of the program. This study aims to identify the reasons why students do not utilize the Free Nutritious Meal (MBG) program based on the (ABC) theory of antecedent, behavior, consequence at SD Negeri 100 Kendari. This research uses a qualitative method with a case study approach. The number of informants to be studied is 6 people selected through Purposive Sampling, consisting of students, the principal, teachers, SPPG officers, and parents. Data collection is conducted through in-depth interviews, recording, observation, and documentation. The data are analyzed through the stages of data reduction, data presentation, and drawing conclusions. Research results show that the antecedent of students' knowledge about the MBG program is at the level of knowing to understanding, the application of the provided menu has been in accordance with balanced nutrition principles, and the program policy is supported by various parties. Students' behavior shows rejection of the program influenced by negative experiences, perceptions of the halalness of food containers, and parental prohibitions. The consequence of students not participating does not directly have a negative impact on their learning conditions or physical health, because nutritional needs are still met from other sources. Therefore, students have no motivation to utilize the program. In conclusion, students who do not take advantage of the MBG program are influenced by perceptions, experiences, and parental restrictions. Therefore, it is necessary to improve education, strengthen communication, and enhance the quality of program implementation to increase the utilization of the MBG program.